2010
DOI: 10.1175/2009jcli2873.1
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Downscaling Forecasts for Winter Monsoon Precipitation in Malaysia Using Multimodel Output Variables

Abstract: This paper compares the skills of four different forecasting approaches in predicting the 1-month lead time of the Malaysian winter season precipitation. Two of the approaches are based on statistical downscaling techniques of multimodel ensembles (MME). The third one is the ensemble of raw GCM forecast without any downscaling, whereas the fourth approach, which provides a baseline comparison, is a purely statistical forecast based solely on the preceding sea surface temperature anomaly. The first multimodel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 27 publications
1
30
0
1
Order By: Relevance
“…Various statistical downscaling schemes have been developed for constructing the relationship between the predictor and the predictand, such as multiple regression models (Wilby et al 1999), artificial neural networks (ANNs) (Harpham and Wilby 2005), canonical correlation analysis (CCA) (Juneng et al 2010), support vector machine (Yu et al 2006), and the singular-value-decomposition (SVD) based statistical downscaling method (Chu et al 2008). The SVD-based statistical downscaling method was used successfully in Taiwan (Chu et al 2008;Chu and Yu 2010) and the East Asia (Paul et al 2008), which was adopted in this work for downscaling monthly rainfall accumulations.…”
Section: Introductionmentioning
confidence: 99%
“…Various statistical downscaling schemes have been developed for constructing the relationship between the predictor and the predictand, such as multiple regression models (Wilby et al 1999), artificial neural networks (ANNs) (Harpham and Wilby 2005), canonical correlation analysis (CCA) (Juneng et al 2010), support vector machine (Yu et al 2006), and the singular-value-decomposition (SVD) based statistical downscaling method (Chu et al 2008). The SVD-based statistical downscaling method was used successfully in Taiwan (Chu et al 2008;Chu and Yu 2010) and the East Asia (Paul et al 2008), which was adopted in this work for downscaling monthly rainfall accumulations.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature several attempts have been carried out in order to forecast precipitation using statistical methods. Juneng et al (2010) compared the skills of four different forecasting approaches in predicting the one-month lead time of the Malaysian winter season precipitation. The results showed that the appropriate downscaling technique and ensemble of various regional climate models (RCM) forecasts could result in some skill enhancement, particularly over peninsular Malaysia, where other models tend to have lower or no skills.…”
Section: Introductionmentioning
confidence: 99%
“…Hazards caused by extreme rainfall often results in extensive evacuation and loss of lives not to mention the destruction of public infrastructure, crop yield damage and economic losses (Juneng et al, 2010). A study on historical data between the years 1975 and 2010 by Syafrina et al (2015) shows increasing trends of extreme rainfall in Peninsular Malaysia.…”
Section: Introductionmentioning
confidence: 99%